Race-Based Sexual Preferences in a Sample of Online Profiles of Urban Men Seeking Sex with Men - White, Jaclyn M. (Springer US, 2014)
Race-based sexual preferences in the online profiles of men who have sex with men (MSM) may be relevant for understanding the sexual health of this population, including racial/ethnic disparities in HIV infection. In October 2011, a content analysis was conducted of the profiles of Boston-area members of a racially diverse website for MSM. The present analysis formatively examined the use of demographic and partner selection criteria by race/ethnicity appearing in the profiles of men who indicated race-based partner preferences (n = 89). Latino men were the most frequently preferred race (54 %), followed by White (52 %), Black (48 %), and Asian (12 %) men. In separate multivariable models adjusted for age and HIV status disclosure, wanting low-risk foreplay was associated with a preference for White men (aOR) = 4.27; 95 % CI = 1.70–10.75; p = 0.002), while wanting group sex was associated with a preference for Black (OR = 2.28; 95 % CI = 1.08–4.81; p = 0.03) and Latino men (OR = 2.56; 95 % CI = 1.25–5.23; p = 0.01). Future studies are needed to replicate findings in larger online samples. Mixed-methods research should explore how racial and behavioral preferences impact the sexual mixing patterns and health of MSM online in urban areas.